A sulfide solid electrolyte with stable cathode interface and a preparation method and application thereof
Patent Information
- Application Number
- CN202610326688.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-03-17
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2046-03-17
AI Technical Summary
[0006]本发明的目的在于提供一种正极界面稳定的硫化物固态电解质及其制备方法和应用,解决了现有技术中固态电池正极界面稳定性较差等问题
首先,本发明提供的正极界面稳定的硫化物固态电解质,其颗粒表面及晶界处的界面物质主要由硫氧化物、磷氧化物、过渡金属硫化物、锂盐类等组成,这些物质的元素主要来源于硫化物固态电解质和正极材料,避免了其他杂元素的引入,降低了界面副反应阻抗。
Smart Images

Figure CN122051402B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium-ion battery technology, and in particular to a sulfide solid electrolyte with a stable positive electrode interface, its preparation method, and its application. Background Technology
[0002] Developing energy storage systems with high stability and high energy-power density is crucial to meeting the ever-growing demand for sustainable energy storage. All-solid-state lithium batteries, which use inherently non-flammable solid-state electrolytes to replace the organic liquid electrolytes in traditional lithium-ion batteries, have been extensively studied due to their high energy density and safety. Among these, all-solid-state lithium batteries composed of sulfide solid-state electrolytes with high ionic conductivity and high-voltage cathode materials are considered the most promising for commercialization.
[0003] However, the structural degradation of high-voltage cathode materials such as high-nickel layered oxide cathode materials during cycling, the side reactions at the interface with sulfide electrolytes with narrow electrochemical windows, the limited charge transport within the composite cathode, and the poor physical contact at the solid-solid interface hinder the application of sulfide-based all-solid-state lithium batteries. Therefore, there is an urgent need for a sulfide solid electrolyte with a stable cathode interface to reduce its continuous oxidation and decomposition during cycling and enhance the physical contact at the cathode solid-solid interface in all-solid-state batteries.
[0004] To address this issue, several documents and patents have proposed methods to improve the interface stability of sulfide solid-state batteries. Common modification methods include coating and elemental doping of the cathode material itself, as seen in Small 21, 32 (2025), eTransportation 25 (2025) 100437, Nat Commun 16, 112 (2025), CN120089807A, CN120089725A, and CN118315557A. However, these methods have limitations. Coating may introduce new phases and interface layers, and while elemental doping improves the stability of the cathode structure, it may generate impurities related to the new doped elements during battery charging and discharging, leading to increased interface impedance. Furthermore, these coating and doping methods are typically complex processes, some requiring high-temperature sintering or atomic layer deposition (ALD), increasing energy consumption or requiring expensive equipment, which is detrimental to large-scale applications.
[0005] In view of this, this application proposes an electrochemically prepared, in-situ stable sulfide solid electrolyte at the positive electrode interface, which can comprehensively solve the above problems. Summary of the Invention
[0006] The purpose of this invention is to provide a sulfide solid electrolyte with a stable cathode interface, its preparation method, and its application, solving the problem of poor cathode interface stability in existing solid-state batteries. This invention cleverly utilizes the characteristics of the initial electrochemical reaction without adding other elements, to generate a sulfide solid electrolyte with a stable cathode interface in situ during the first charge-discharge process of the sulfide solid electrolyte and cathode material under a specific program. Through three main mechanisms—electrochemical oxidation, SO2 exchange, and transition metal migration—an interface material, composed of sulfur oxides, phosphorus oxides, transition metal sulfides, lithium salts, and other substances, is electrochemically generated in situ on the surface and grain boundaries of the sulfide solid electrolyte particles. This interface material has a thickness of 5-50 nm, and its content forms a gradient along the direction perpendicular to the interface between the sulfide solid electrolyte and the cathode material, with the highest concentration at the interface. The in-situ generated interface material of this invention not only enhances the contact between the electrolyte and the positive electrode particles, but also weakens the further oxidation and decomposition of the sulfide solid electrolyte during cycling, thereby improving the stability of the solid-solid interface contact of the positive electrode. Furthermore, when applied to solid-state batteries, it exhibits excellent electrochemical performance, meets the requirements of high-energy-density all-solid-state batteries, and has good application prospects.
[0007] In order to achieve the above-mentioned objectives of the present invention, the following technical solution is adopted: In a first aspect, the present invention provides a method for preparing a sulfide solid electrolyte with a stable positive electrode interface, comprising the following steps: (1) A composite positive electrode is prepared by mixing a sulfide solid electrolyte with a positive electrode active material, and an all-solid-state battery is prepared in the order of composite positive electrode, sulfide solid electrolyte layer and negative electrode; wherein the mass ratio of sulfide solid electrolyte to positive electrode active material is 10~50:50~90; the sulfide solid electrolyte layer is mainly formed by pressing sulfide solid electrolyte, and the thickness of the sulfide solid electrolyte layer is 400~900μm; the negative electrode is lithium metal or lithium indium alloy; (2) Perform the first charge and discharge of the all-solid-state battery and set the charge and discharge program: The charging procedure is as follows: charge at a current of 0.05~0.1C for 10~15 minutes, rest for 10~30 minutes, then continue charging at a current of 0.05~0.1C for 10~15 minutes, and rest for another 10~30 minutes. Repeat the above process until the charging voltage reaches 4.6V. vs. Li + / Li), stop charging; The discharge procedure is as follows: discharge at a current of 0.05~0.1C for 10~15 minutes, rest for 10~30 minutes, then continue discharging at a current of 0.05~0.1C for 10~15 minutes, and rest for another 10~30 minutes. Repeat the above process until the discharge voltage reaches 1.6V.vs. Li + ( / Li), stop discharging, and obtain a battery with a stable sulfide solid electrolyte at the positive electrode interface.
[0008] In some embodiments, the sulfide solid electrolyte in step (1) is Li2SnS3, Li3PS4, Li7PS6, or Li7P3S. 11 Li6PS5Cl, Li6PS5Br, Li 5.5 PS 4.5 Cl 1.5 Li 10 GeP2S 12 Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 One or more of them.
[0009] In some embodiments, the positive electrode active material in step (1) is LiFePO4, LiCoO2, LiNiO2, LiMnO2, or LiCo. x Ni y O2 (where 0 < x <1, 0< y <1) LiNi x Co y M 1-x-y O2 (where M is at least one of Mn, Al, Mg, Ga, Cr, Cu, Zn, and Mo, 0 ≤ x <1, 0 ≤ y One or more of the following: <1).
[0010] In some implementations, the charging / discharging current density in step (2) is 0.05~0.3 mA cm⁻¹. -2 .
[0011] Secondly, the present invention provides a sulfide solid electrolyte with a stable positive electrode interface obtained by the above preparation method.
[0012] The positive electrode interface is stable. The sulfide solid electrolyte particles have electrochemically generated interfacial substances such as sulfur oxides, phosphorus oxides, transition metal sulfides, and lithium salts on their surface and at the grain boundaries. Furthermore, the sulfur oxides mainly include elemental sulfur (S) and polysulfides (Li₂S). x ,2≤x≤8), sulfur oxides (sulfites (SO3) 2- ), sulfate (SO4) 2- One or a combination of the following: ) ...""" ) "" ) "" "" """ """""""""""""""""""""""""""""""""""""
[0013] Furthermore, the phosphorus oxides mainly include lithium phosphate (Li3PO4) and P2O6. 4- PO3S 4- PO2S2 4- One or a combination of them.
[0014] Furthermore, the transition metal sulfides mainly include NiS, CoS / Co3S4, MnS, and mixed transition metal sulfophosphides (transition metal ions and PS4). 3- One or a combination of the following: (complex compounds generated by the reaction).
[0015] Furthermore, the lithium salts mainly include one or a combination of Li2S, LiCl, Li3P, Li2CO3, etc.
[0016] Furthermore, the molar ratio of sulfur oxides, phosphorus oxides, transition metal sulfides, and lithium salts in the interfacial material is 0.005%~0.02% : 0.005%~0.01% : 0.001%~0.01% : 0.008%~0.05% (the percentage represents the molar proportion of the sulfide solid electrolyte); the total amount of interfacial material to the molar ratio of the sulfide solid electrolyte is 0.05%~0.2%.
[0017] Furthermore, the interfacial material is formed through three main mechanisms: electrochemical oxidation, SO exchange, and transition metal migration.
[0018] Furthermore, the electrochemical oxidation provides a strong oxidizing environment for the high-voltage positive electrode.
[0019] Furthermore, the SO exchange refers to the exchange of lattice oxygen released by the cathode material during charging and discharging with sulfur in the sulfide solid electrolyte.
[0020] Furthermore, the transition metal migration is the release of Ni from the cathode material under high voltage due to lattice instability. 2+ / Co 2+ / Mn 2+ These ions diffuse to the electrolyte interface and combine with sulfur ions to form corresponding sulfides.
[0021] Furthermore, the thickness of the interface material is 5~50nm, and the content of the interface material forms a gradient in the sulfide solid electrolyte and the cathode material along the direction perpendicular to the interface between the two, with the highest concentration at the interface.
[0022] Furthermore, the particle size D50 of the sulfide solid electrolyte is 0.2~5μm, the particle size D50 of the positive electrode active material is 2~12μm, and the depth of gradient penetration of the interface material in the vertical direction at the interface between the two is 10~100nm.
[0023] Thirdly, the present invention also provides an application of the above-mentioned positive electrode interface-stable sulfide solid electrolyte in an all-solid-state lithium battery.
[0024] Beneficial effects First, the sulfide solid electrolyte with a stable cathode interface provided by the present invention is mainly composed of sulfur oxides, phosphorus oxides, transition metal sulfides, lithium salts, etc. on the particle surface and at the grain boundaries. The elements of these substances mainly come from the sulfide solid electrolyte and the cathode material, avoiding the introduction of other impurities and reducing the impedance of interfacial side reactions.
[0025] Secondly, the sulfide solid electrolyte with a stable cathode interface provided by this invention generates interfacial substances on the particle surface and grain boundaries in situ via three main mechanisms: electrochemical oxidation, SO2 exchange, and transition metal migration. The content of these interfacial substances forms a gradient along the direction perpendicular to the interface between the sulfide solid electrolyte and the cathode material, with the highest concentration at the interface. This in-situ generated interfacial substance not only enhances the contact between the electrolyte and the cathode particles but also weakens further oxidative decomposition of the sulfide solid electrolyte during cycling, thus improving the stability of the cathode solid-solid interface.
[0026] Finally, the method for preparing a sulfide solid electrolyte with a stable cathode interface provided by this invention involves in-situ generation of the sulfide solid electrolyte and cathode material during the first charge-discharge process under a specific procedure. This method requires no expensive equipment and is simple and easy to implement. It only requires setting an extra step before testing the assembled battery; this special procedure yields a sulfide solid electrolyte with a stable cathode interface. Subsequent cycle testing of the battery assembled using this sulfide solid electrolyte can improve the cycle stability of the all-solid-state lithium battery.
[0027] In summary, this invention can improve the solid-solid interface problem between sulfide solid electrolyte and cathode material in existing all-solid-state lithium batteries, improve the stability of sulfide solid electrolyte to cathode material, and enable sulfide solid electrolyte to be better applied in all-solid-state lithium batteries, while exhibiting excellent cycle stability.
[0028] The present invention has been described in detail above; however, the above embodiments are merely illustrative in nature and are not intended to limit the invention. Furthermore, this document is not limited to the foregoing prior art or the invention itself, or to any theory described in the following embodiments. Attached Figure Description
[0029] Figure 1 This is a cycle performance diagram of the all-solid-state lithium battery assembled with a sulfide solid electrolyte obtained in Example 1 of the present invention; Figure 2The diagram shows the cycle performance of the all-solid-state lithium battery assembled with sulfide solid electrolyte obtained in Comparative Example 1 of this invention. Detailed Implementation
[0030] The present invention will be further described below with reference to the embodiments. It should be noted that the following embodiments are provided for illustrative purposes only and do not constitute a limitation on the scope of protection of the present invention.
[0031] Unless otherwise specified, the raw materials, reagents, and methods used in the embodiments are all conventional raw materials, reagents, and methods in the art.
[0032] Example 1 This embodiment provides a sulfide solid electrolyte with a stable positive electrode interface and its preparation method, wherein the sulfide solid electrolyte is Li 5.5 PS 4.5 Cl 1.5 The particle size D50 is 0.68 μm, and the positive electrode active material is LiNi. 0.8 Co 0.1 Mn 0.1 O2 with a particle size D50 of 10 μm was used to prepare a composite positive electrode by mixing a sulfide solid electrolyte and a positive electrode active material at a mass ratio of 15%:85%. A sulfide all-solid-state battery with a lithium-indium alloy negative electrode was then assembled, where the sulfide solid electrolyte layer had a thickness of 750 μm. The specific preparation process is as follows: The sulfide solid electrolyte and the positive electrode active material were mixed at a mass ratio of 15%:85% and ground in a mortar for 30 minutes to prepare a composite positive electrode. The sulfide solid electrolyte was first placed in a solid-state battery mold with an inner diameter of 10 mm and pressed into a sheet with a thickness of 750 μm. 10 mg of the composite positive electrode material was then loaded onto one side and pressurized at 370 MPa for 5 minutes. Next, a lithium-indium alloy was loaded onto the other side and pressurized at 180 MPa for 5 minutes to obtain the final sulfide all-solid-state battery.
[0033] The procedure for the first charge and discharge test of the battery is as follows: The charging program is set as follows: charge at 0.06C for 12 minutes, rest for 20 minutes, then continue charging at 0.06C for 12 minutes, rest for another 20 minutes, and repeat the above process until the charging voltage reaches 4.6V. vs. Li + / Li), charging stopped, charging current density was 0.106 mA cm⁻¹ -2 ; The discharge program is set as follows: discharge at a current of 0.06C for 12 minutes, rest for 20 minutes, then continue discharging at a current of 0.06C for 12 minutes, and rest for another 20 minutes. Repeat the above process until the discharge voltage reaches 1.6V. vs. Li+ / Li), discharge stops, discharge current density is 0.106 mA cm⁻¹ -2 .
[0034] Example 2 This embodiment provides a sulfide solid electrolyte with a stable positive electrode interface and its preparation method. The sulfide solid electrolyte is Li6PS5Cl with a particle size D50 of 0.9 μm, and the positive electrode active material is LiNi. 0.9 Co 0.05 Mn 0.05 O2, with a particle size D50 of 8 μm, is used to prepare a composite positive electrode by mixing a sulfide solid electrolyte and a positive electrode active material at a mass ratio of 20%:80%, and assembling a sulfide all-solid-state battery with a lithium indium alloy as the negative electrode. The thickness of the sulfide solid electrolyte layer is 500 μm (the specific preparation process is the same as in Example 1).
[0035] The procedure for the first charge and discharge test of the battery is as follows: The charging program is set as follows: charge at 0.08C for 15 minutes, rest for 25 minutes, then continue charging at 0.08C for 15 minutes, rest for another 25 minutes, and repeat the above process until the charging voltage reaches 4.6V. vs. Li + / Li), charging stopped, charging current density was 0.143 mA cm⁻¹ -2 ; The discharge program is set as follows: discharge at a current of 0.08C for 15 minutes, rest for 25 minutes, then continue discharging at a current of 0.08C for 15 minutes, and rest for another 25 minutes. Repeat the above process until the discharge voltage reaches 1.6V. vs. Li + / Li), discharge stopped, discharge current density was 0.143 mA cm⁻¹ -2 .
[0036] Example 3 This embodiment provides a sulfide solid electrolyte with a stable positive electrode interface and its preparation method. The sulfide solid electrolyte is Li6PS5Br with a particle size D50 of 2 μm, and the positive electrode active material is LiNi. 0.6 Co 0.2 Mn 0.2 O2, with a particle size D50 of 5 μm, is used to prepare a composite positive electrode by mixing a sulfide solid electrolyte and a positive electrode active material at a mass ratio of 25%:75%, and assembling a sulfide all-solid-state battery with a lithium indium alloy as the negative electrode. The thickness of the sulfide solid electrolyte layer is 600 μm (the specific preparation process is the same as in Example 1).
[0037] The procedure for the first charge and discharge test of the battery is as follows: The charging program is set as follows: charge at 0.1C for 10 minutes, rest for 10 minutes, then continue charging at 0.1C for 10 minutes, rest for another 10 minutes, and repeat the above process until the charging voltage reaches 4.6V. vs. Li + / Li), charging stopped, charging current density was 0.178 mA cm⁻¹ -2 ; The discharge program is set as follows: discharge at 0.1C for 10 minutes, rest for 10 minutes, then continue discharging at 0.1C for 10 minutes, rest for 10 minutes, and repeat the above process until the discharge voltage reaches 1.6V. vs. Li + / Li), discharge stops, discharge current density is 0.178 mA cm⁻¹ -2 .
[0038] Example 4 This embodiment provides a sulfide solid electrolyte with a stable positive electrode interface and its preparation method, wherein the sulfide solid electrolyte is Li7P3S. 11 The particle size D50 is 3μm, and the positive electrode active material is LiNi. 0.5 Co 0.3 Mn 0.2 O2, with a particle size D50 of 8 μm, is used to prepare a composite positive electrode by mixing a sulfide solid electrolyte and a positive electrode active material at a mass ratio of 30%:70%, and assembling a sulfide all-solid-state battery with a lithium indium alloy as the negative electrode. The thickness of the sulfide solid electrolyte layer is 700 μm (the specific preparation process is the same as in Example 1).
[0039] The procedure for the first charge and discharge test of the battery is as follows: The charging program is set as follows: charge at 0.05C for 15 minutes, rest for 15 minutes, then continue charging at 0.05C for 15 minutes, rest for 15 minutes again, and repeat the above process until the charging voltage reaches 4.6V. vs. Li + / Li), charging stopped, charging current density was 0.089 mA cm⁻¹ -2 ; The discharge program is set as follows: discharge at a current of 0.05C for 15 minutes, rest for 15 minutes, then continue discharging at a current of 0.05C for 15 minutes, and rest for 15 minutes. Repeat the above process until the discharge voltage reaches 1.6V. vs. Li + / Li), discharge stopped, discharge current density was 0.089 mA cm⁻¹ -2 .
[0040] Example 5 This embodiment provides a sulfide solid electrolyte with a stable positive electrode interface and its preparation method, wherein the sulfide solid electrolyte is Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 The particle size D50 is 1.5 μm, and the positive electrode active material is LiNi. 0.8 Co 0.1 Mn 0.1 O2, with a particle size D50 of 5 μm, is used to prepare a composite positive electrode by mixing a sulfide solid electrolyte and a positive electrode active material at a mass ratio of 35%:65%, and assembling a sulfide all-solid-state battery with a lithium indium alloy as the negative electrode. The thickness of the sulfide solid electrolyte layer is 650 μm (the specific preparation process is the same as in Example 1).
[0041] The procedure for the first charge and discharge test of the battery is as follows: The charging program is set as follows: charge at 0.05C for 15 minutes, rest for 30 minutes, then continue charging at 0.05C for 15 minutes, rest for another 30 minutes, and repeat the above process until the charging voltage reaches 4.6V. vs. Li + / Li), charging stopped, charging current density was 0.089 mA cm⁻¹ -2 ; The discharge program is set as follows: discharge at a current of 0.05C for 15 minutes, rest for 30 minutes, then continue discharging at a current of 0.05C for 15 minutes, and rest for another 30 minutes. Repeat the above process until the discharge voltage reaches 1.6V. vs. Li + / Li), discharge stopped, discharge current density was 0.089 mA cm⁻¹ -2 .
[0042] Comparative Example 1 An all-solid-state battery was assembled using the same sulfide solid electrolyte, positive electrode, and negative electrode as in Example 1, except that the specific charge and discharge program settings were not performed, while other parameters were the same as in Example 1.
[0043] Comparative Example 2 An all-solid-state battery was assembled using the same sulfide solid electrolyte, positive electrode, and negative electrode as in Example 1, except that the sulfide solid electrolyte and positive electrode active material were in a mass ratio of 5%:95%, while other parameters were the same as in Example 1.
[0044] Comparative Example 3 An all-solid-state battery was assembled using the same sulfide solid electrolyte, positive electrode, and negative electrode as in Example 1, except that the thickness of the sulfide solid electrolyte layer was 300 μm, while other parameters were the same as in Example 1.
[0045] Comparative Example 4 An all-solid-state battery was assembled using the same sulfide solid electrolyte, positive electrode, and negative electrode as in Example 1, except that the charging program was set as follows: charge at 0.2C for 20 minutes, rest for 60 minutes, then continue charging at 0.2C for 20 minutes, and rest for another 60 minutes, repeating the above process until the charging voltage reaches 4.6V. vs. Li + / Li), stop charging, other parameters are the same as in Example 1.
[0046] Comparative Example 5 An all-solid-state battery was assembled using the same sulfide solid electrolyte, positive electrode, and negative electrode as in Example 1. The difference was that the discharge program was set as follows: discharge at 0.2C for 20 minutes, rest for 60 minutes, then continue discharging at 0.2C for 20 minutes, and rest for another 60 minutes, repeating the above process until the discharge voltage reached 1.6V. vs. Li + / Li), stop discharging, and other parameters are the same as in Example 1.
[0047] Experimental Example Testing of all-solid-state lithium batteries: The batteries obtained in Examples 1-5 and Comparative Examples 2-5 were subjected to subsequent tests. The subsequent test procedure was set as follows: the test voltage range was 2.6~4.4V. vs. Li + / Li), at 1C (1C = 200 mA g), -1 Long-cycle performance tests were conducted at current density, and the capacity retention rate for the corresponding number of cycles was recorded.
[0048] The battery from Comparative Example 1 that did not undergo this specific first charge and discharge cycle was subjected to the following test, with the test procedure set as follows: the test voltage range was 2.6~4.4V ( vs. Li + The system ( / Li) underwent its first charge-discharge cycle at 0.1C, followed by long-cycle performance testing at 1C, and the capacity retention rate for each cycle was recorded. All tests were conducted at 25℃.
[0049] Table 1. Performance data of all-solid-state lithium batteries in Examples 1-5 and Comparative Examples 1-5
[0050] Analysis of the data in Table 1 shows that the all-solid-state lithium battery composed of a sulfide solid electrolyte with a stable cathode interface obtained by the preparation method of this application exhibits excellent long-term cycle stability. This is due to the interfacial material, composed of sulfur oxides, phosphorus oxides, transition metal sulfides, lithium salts, and other substances, which is electrochemically generated in situ on the surface and grain boundaries of the sulfide solid electrolyte particles of this invention. This interfacial material not only enhances the contact between the electrolyte and the cathode particles but also weakens the further oxidation and decomposition of the sulfide solid electrolyte during cycling, thereby improving the stability of the cathode solid-solid interface contact.
[0051] Comparing Example 1 and Comparative Example 1, it was found that the stability of the cathode interface of the sulfide solid electrolyte was significantly improved after the first charge-discharge cycle under a specific procedure. At the same time, the long-cycle stability of the all-solid-state lithium battery was also significantly improved. This fully demonstrates that improving the stability of the cathode interface is crucial to the overall performance of the all-solid-state battery.
[0052] In Comparative Examples 2-5, the sulfide solid electrolyte and cathode material were the same, but the preparation process and program settings were different. The electrochemical performance of the all-solid-state lithium batteries assembled with the obtained sulfide solid electrolytes was different. This shows that only under specific conditions and parameters can a sulfide electrolyte with a stable cathode interface be obtained and good performance be achieved.
[0053] The above embodiments are merely illustrative of the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein, without departing from the spirit and substance defined by the claims of the present invention; and such modifications or substitutions are still within the scope defined by the claims of the present invention.
Claims
1. A method for preparing a sulfide solid electrolyte with a stable positive electrode interface, characterized in that, Includes the following steps: (1) A composite positive electrode is prepared by mixing a sulfide solid electrolyte with a positive electrode active material, and an all-solid-state battery is prepared in the order of composite positive electrode, sulfide solid electrolyte layer, and negative electrode; wherein the mass ratio of sulfide solid electrolyte to positive electrode active material in the composite positive electrode is 10~50:50~90; the sulfide solid electrolyte layer is mainly formed by pressing sulfide solid electrolyte, and the thickness of the sulfide solid electrolyte layer is 400~900μm; the negative electrode is lithium metal or lithium indium alloy. (2) Perform the first charge and discharge of the all-solid-state battery and set the charge and discharge program: The charging procedure is as follows: charge at a current of 0.05~0.1C for 10~15 minutes, rest for 10~30 minutes, then continue charging at a current of 0.05~0.1C for 10~15 minutes, and then rest for 10~30 minutes. Repeat the above process until the charging voltage reaches 4.6V, then stop charging. The discharge procedure is as follows: discharge at a current of 0.05~0.1C for 10~15 minutes, rest for 10~30 minutes, then continue to discharge at a current of 0.05~0.1C for 10~15 minutes, and then rest for 10~30 minutes. Repeat the above process until the discharge voltage reaches 1.6V, then stop discharging to obtain a battery with a sulfide solid electrolyte with a stable positive electrode interface. The sulfide solid electrolyte mentioned in step (1) is Li7P3S 11 Li6PS5Cl, Li6PS5Br, Li 5.5 PS 4.5 Cl 1.5 Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 One or more of them; The positive electrode active material mentioned in step (1) is LiNi x Co y M 1-x-y O2, where M is Mn, 0 < x ≤0.9, 0< y ≤0.3; In step (1), the particle size D50 of the sulfide solid electrolyte is 0.2~5μm, and the particle size D50 of the positive electrode active material is 2~12μm.
2. The preparation method according to claim 1, characterized in that, In step (2), the charging and discharging current density is 0.05~0.3 mA·cm. -2 .
3. A sulfide solid electrolyte with a stable positive electrode interface, characterized in that, It is prepared by the preparation method described in claim 1 or 2.
4. The positive electrode interface-stable sulfide solid electrolyte according to claim 3, characterized in that, The positive electrode interface is stable. The sulfide solid electrolyte particles have electrochemically generated interface substances on their surface and at the grain boundaries.
5. The positive electrode interface-stable sulfide solid electrolyte according to claim 4, characterized in that, The thickness of the interface material is 5~50nm.
6. The application of a positive electrode interface-stable sulfide solid electrolyte as described in any one of claims 3-5 in an all-solid-state lithium battery.
Citation Information
Patent Citations
Modified high-nickel positive electrode material, preparation method thereof and sulfide all-solid-state battery
CN118315557A
Chloride-coated modified positive electrode material, preparation method thereof and sulfide all-solid-state battery
CN120089725A
Method for improving interface stability of sulfide all-solid-state battery
CN120089807A
Sulfide solid electrolyte with core-shell structure, preparation method and solid battery
CN110459798A
Positive electrode material, positive electrode, solid-state battery and preparation method thereof
CN117747816A